Myocardial Infarction and AGT p.Thr174Met Polymorphism: A Meta-Analysis of 7657 Subjects - Yan-yan Li; Hui Wang; Hao Wang; Yang-yang Zhang (Cardiovascular Therapeutics)
Background. It has been suggested that the angiotensinogen (AGT) gene rs4762 (p.Thr174Met) polymorphism might be associated with myocardial infarction (MI) risk, but the study results are still debatable. Objective and Methods. In order to explore the relationship between AGT p.Thr174Met polymorphism and MI risk, the current meta-analysis involving 7657 subjects from 11 individual studies was conducted. Results. A significant association between AGT p.Thr174Met polymorphism and MI was found under recessive (OR: 2.26, 95% CI: 1.35-3.77, P=0.002), dominant (OR: 1.131, 95% CI: 1.016-1.260, P=0.024), codominant (OR: 2.198, 95% CI: 1.334-3.621, P=0.002), and additive (OR: 1.363, 95% CI: 1.132-1.641, P=0.001) genetic models. In the Asian subgroup, significantly increased MI risk was found under all genetic models (P<0.05). No significant association between AGT p.Thr174Met polymorphism and MI was found under all genetic models in the Caucasian subgroup (P>0.05). Conclusions. AGT p.Thr174Met variant might increase MI risk, especially within the Asian population. The Met174 allele of AGT p.Thr174Met might confer the risk for MI.